Multiculturalism Reconsidered. Bilingual Education in Guatemala - Drozdowicz, Jarema (Kultura-Społeczeństwo-Edukacja, 2015)
The modern Maya movement is an example of a new sort of indigenous cultural activism. The long lasting struggle for indigenous rights had finally led to the renegotiation of the social, legal and political order in countries like Guatemala and Mexico. Today we witness a vibrant indigenous activism in many fields, like education for example. This paper deals with the issue of multicultural education in the mentioned countries, but also it presents critical problems of a wider process – i.e. regaining cultural freedom after 500 years of marginalization.